A kind of polyurethane rigid foam material and preparation method thereof

By dehydrating the polyether substances and using low boiling point foaming agents, the problems of high thermal conductivity of CO2 and physical foaming agent volatility in polyurethane hard foaming materials are solved, and better insulation effect and mechanical properties are achieved.

CN118791692BActive Publication Date: 2025-03-14ZHONGSHAN BASD CHEM TECH CO LTD +4
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410791958.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-19
Publication Date
2025-03-14
Estimated Expiration
2044-06-19

AI Technical Summary

Technical Problem

The thermal insulation performance of existing polyurethane hard foam materials is not satisfactory, mainly due to the high thermal conductivity of CO2 and the volatility of physical foaming agents, which leads to a high thermal conductivity, affecting the insulation effect of the material.

Method used

By dehydrating polyether substances, the addition of water is reduced, the influence of heat generated by moisture and carbon dioxide is eliminated, and a combination of a variety of low-boiling point foaming agents is introduced to control the uniformity and stability of the foaming process.

Benefits of technology

It effectively reduces the thermal conductivity of the material, improves the thermal insulation effect and mechanical properties of the foam, and ensures the stability of the foaming process and the consistency of material performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118791692B_ABST
    Figure CN118791692B_ABST
Patent Text Reader

Abstract

The present invention provides a polyurethane rigid foam material and a preparation method thereof, belonging to the technical field of polyurethane rigid foam. The preparation method comprises: dehydrating a polyether substance; preparing a combined polyether mixture; preparing a polymerized MDI mixture; and mixing the combined polyether mixture with the polymerized MDI mixture to obtain the polyurethane rigid foam material. The present invention dehydrates the polyether substance to eliminate the influence of heat and carbon dioxide generated by the addition of water, and adds a combination of multiple low-boiling point foaming agents, thereby maintaining the toughness of the foam and greatly reducing the thermal conductivity of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyurethane rigid foam materials, and in particular relates to a polyurethane rigid foam material and a preparation method thereof. Background Art

[0002] Polyurethane is a polymer material widely used in many fields and has attracted much attention due to its excellent physical and chemical properties. Polyurethane materials can be divided into many types, such as soft foam, hard foam, elastomer, coating, adhesive, etc. Among them, polyurethane rigid foam has been widely used in building insulation, cold chain transportation, household appliances and other fields due to its superior thermal insulation performance, good mechanical strength and chemical stability. Polyurethane rigid foam is a polymer network structure generated by chemical reaction of polyols and isocyanates in the presence of catalysts, foaming agents, surfactants and other additives. The formation of bubbles is crucial to the thermal insulation effect of the foam.

[0003] In the existing polyurethane rigid foam preparation process, water is mainly used as one of the foaming agents, and water and isocyanate react to generate carbon dioxide (CO2) gas to form foam. The reaction process is as follows: -RNCO+H2O→-RNHCOOH→-RNH2+CO2.

[0004] The reaction not only produces CO2 gas, but also releases heat, which can volatilize the physical foaming agent into gas and become part of the foam, thereby enhancing the thermal insulation effect of the foam. In addition, the amine generated by the reaction of water and isocyanate will further react with isocyanate to form a urea bond structure, increase the cross-linking density of the material, and improve the mechanical strength of the foam. This process enables polyurethane rigid foam to have higher mechanical properties and thermal insulation properties.

[0005] However, there are some obvious defects and problems in the existing technology. First, the thermal conductivity of CO2 is relatively high, about 0.0353 W / mK, which is nearly three times higher than other commonly used physical foaming agents (such as hydrofluorocarbons, fluorinated hydrocarbons, etc.). This means that when CO2 is the main component in the bubbles, although it can form a foam structure, its thermal insulation performance is relatively poor, resulting in a high thermal conductivity of the foam as a whole, affecting the thermal insulation effect of the material. Secondly, physical foaming agents are easy to volatilize under high temperature conditions, resulting in instability in the foaming process, further affecting the uniformity of the foam and the stability of its performance.

[0006] In general, the main problems of the prior art are the high thermal conductivity of CO2 and the volatility of physical foaming agents, which together lead to unsatisfactory thermal insulation performance of polyurethane rigid foam. In addition, although the heat generated during the foaming process can promote the gasification of the physical foaming agent, it is difficult to control this thermal effect, which can easily lead to uneven foaming process and affect the quality and performance of the final product. These defects not only limit the application of polyurethane rigid foam in certain fields, but also increase the complexity and cost of the preparation process.

[0007] Therefore, in order to improve the performance of polyurethane rigid foam, the existing technology needs to find a foaming agent that replaces CO2 to reduce the thermal conductivity of the foam and improve its thermal insulation effect. At the same time, how to stably control the heat generated during the foaming process to ensure the uniformity of the foaming process and the stability of material properties has also become a research focus. Only by solving these problems can the advantages of polyurethane rigid foam in various fields be further exerted, its application scope can be expanded, and its market competitiveness can be improved. Summary of the invention

[0008] In order to solve the above problems, the present invention provides a method for preparing a polyurethane rigid foam material, comprising:

[0009] Dehydration treatment of polyether substances;

[0010] Respectively prepare a polyether substance, a catalyst system mixture, a first low-boiling point blowing agent, a second low-boiling point blowing agent, a tertiary amine catalyst, a quality assurance agent and polymeric MDI, and divide the first low-boiling point blowing agent into part A and part B, and divide the second low-boiling point blowing agent into part C and part D;

[0011] A combined polyether mixture is prepared by using the dehydrated polyether substance, the catalyst system mixture, part A of the first low-boiling point foaming agent, part C of the second low-boiling point foaming agent, the tertiary amine catalyst and the quality assurance agent;

[0012] A polymeric MDI mixture is prepared using the polymeric MDI, part B of the first low-boiling point foaming agent, and part D of the second low-boiling point foaming agent;

[0013] The combined polyether mixture and the polymerized MDI mixture are mixed and reacted to obtain the polyurethane rigid foam material;

[0014] Preferably, in the combined polyether mixture, the weight proportions of the various raw materials are respectively:

[0015] Polyether substances after dehydration treatment 74-95.5;

[0016] Catalytic system mixture 1-2;

[0017] 0-5% of the A portion of the first low boiling point blowing agent;

[0018] Part C 1-15 of the second low boiling point blowing agent;

[0019] Tertiary amine catalyst 0.5-1;

[0020] Preservative 2-3.

[0021] Preferably, in the polymeric MDI mixture, the weight proportions of the various raw materials are respectively:

[0022] Polymeric MDI 80-100;

[0023] 0-5% of the B portion of the first low boiling point blowing agent;

[0024] The second low boiling point blowing agent contains 0-15 parts of D.

[0025] Preferably, the total weight percentage of A, B, C and D is 15-20;

[0026] Preferably, in the mixing reaction of the combined polyether mixture and the polymeric MDI mixture, the weight ratio of the polymeric MDI mixture to the combined polyether mixture is 1.2:1.

[0027] Preferably, the dehydration treatment is performed by heating and vacuum drying;

[0028] Preferably, the vacuum degree of the dehydration treatment is 0.02 MPA-0.04 MPA;

[0029] Preferably, the temperature of the dehydration treatment is 60°C-80°C;

[0030] Preferably, the dehydration time of the dehydration treatment is 60 min-90 min;

[0031] Preferably, the standard of the dehydration treatment is: controlling the water content of the polyether substance to be no greater than 0.01.

[0032] Preferably, the polyether substance comprises:

[0033] OTDA polyether, polyester, sorbitol polyether, silicone oil and amine catalyst;

[0034] Preferably, the polyether material includes the following components in parts by weight:

[0035] OTDA polyether 56-77.5;

[0036] Polyester 10-20;

[0037] Sorbitol polyether 10-20;

[0038] Silicone oil 1.5-2;

[0039] Amine catalyst 1-2.

[0040] Preferably, the catalyst system mixture comprises:

[0041] Organotins, organobismuths, and perfluoroolefins;

[0042] Preferably, the catalyst system mixture includes the following components in parts by weight:

[0043] Organic tin 5-40;

[0044] Organic bismuth 5-40;

[0045] Perfluoroolefin 20-90.

[0046] Preferably, the first low boiling point blowing agent is selected from at least one of pentane, methyl formate, HFC-245fa, LBA, R600, R600a, R152a, R134a, R1234yf, opteon 1100 / 1150, HCFO-1224yd, HCFO-1234ze, HCFO-1243zf, HCFO-1233xf and trifluoropropylene.

[0047] Preferably, the second low-boiling-point blowing agent comprises neopentane, tetramethylsilane and hexafluoropropylene;

[0048] Preferably, the second low-boiling point foaming agent includes the following components in parts by weight:

[0049] Neopentane 5-20;

[0050] Tetramethylsilane 5-50;

[0051] Hexafluoropropylene 60-90.

[0052] Preferably, the tertiary amine catalyst is TOYOCAT-SX60.

[0053] Preferably, the preservative comprises:

[0054] isotridecyl alcohol and cocamide;

[0055] Preferably, the preservative includes the following components in parts by weight:

[0056] Isotridecyl alcohol 20-50;

[0057] Cocamide 50-80.

[0058] Preferably, the mixing reaction of the combined polyether mixture and the polymeric MDI mixture further comprises:

[0059] Perform microwave heating during the reaction;

[0060] Preferably, the microwave heating treatment time is: heating to 30-200 seconds after the reaction starts;

[0061] Preferably, the frequency of the microwave heating treatment is: 1.5 GHz -3.2 GHz.

[0062] In addition, in order to solve the above problems, the present invention also provides a polyurethane rigid foam material, which is prepared by the preparation method of the polyurethane rigid foam material as described above.

[0063] The present invention provides a polyurethane rigid foam material and a preparation method thereof. The preparation method of the polyurethane rigid foam material comprises dehydrating a polyether substance; preparing a polyether substance, a catalyst system mixture, a first low-boiling point foaming agent, a second low-boiling point foaming agent, a tertiary amine catalyst, a quality-keeping agent and polymerized MDI respectively, and dividing the first low-boiling point foaming agent into part A and part B, and dividing the second low-boiling point foaming agent into part C and part D; preparing a combined polyether mixture using the dehydrated polyether substance, the catalyst system mixture, part A of the first low-boiling point foaming agent, part C of the second low-boiling point foaming agent, the tertiary amine catalyst and the quality-keeping agent; preparing a polymerized MDI mixture using the polymerized MDI, part B of the first low-boiling point foaming agent and part D of the second low-boiling point foaming agent; and mixing the combined polyether mixture with the polymerized MDI mixture to obtain the polyurethane rigid foam material. The invention performs dehydration treatment on the polyether material to eliminate the influence of heat and carbon dioxide generated by the addition of water, and adds a combination of multiple low-boiling point foaming agents to maintain the foam toughness and greatly reduce the thermal conductivity of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 The schematic diagram is a process flow diagram of the method for preparing the polyurethane rigid foam material of the present invention;

[0065] Figure 2 It is a schematic diagram of the thermal conductivity results of the embodiment and the comparative example in comparative example experiment 2 of the preparation method of the polyurethane rigid foam material of the present invention;

[0066] Figure 3 It is a schematic diagram of the thermal conductivity results of the examples and comparative examples at different altitudes in comparative experiment 5 of the method for preparing the polyurethane rigid foam material of the present invention.

[0067] Reference numerals: DETAILED DESCRIPTION

[0068] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0069] refer to Figure 1 In an embodiment of the present application, a method for preparing a polyurethane rigid foam material is provided, comprising:

[0070] Step S1, dehydrating the polyether material;

[0071] Step S2, respectively preparing a polyether substance, a catalyst system mixture, a first low-boiling point foaming agent, a second low-boiling point foaming agent, a tertiary amine catalyst, a quality-preserving agent and polymeric MDI, and dividing the first low-boiling point foaming agent into part A and part B, and dividing the second low-boiling point foaming agent into part C and part D;

[0072] Step S3, preparing a combined polyether mixture using the dehydrated polyether substance, the catalyst system mixture, part A of the first low-boiling point foaming agent, part C of the second low-boiling point foaming agent, the tertiary amine catalyst and the quality assurance agent;

[0073] Step S4, preparing a polymeric MDI mixture using the polymeric MDI, part B of the first low-boiling point foaming agent and part D of the second low-boiling point foaming agent;

[0074] Step S5, mixing the combined polyether mixture and the polymerized MDI mixture to obtain the polyurethane rigid foam material;

[0075] It should be noted that polyurethane materials are widely used in various fields due to their excellent physical and chemical properties, especially in building insulation and cold chain transportation. Polyurethane rigid foam is a polymer network structure generated by chemical reaction of polyols and isocyanates under the action of catalysts, foaming agents, surfactants and other additives. The formation of bubbles in its preparation process is crucial to the thermal insulation effect of the foam. In the existing polyurethane rigid foam preparation method, water, as one of the essential components, plays a key role.

[0076] In the existing method for preparing rigid polyurethane foam, the addition of water is inevitable because water generates carbon dioxide (CO2) gas and releases heat when reacting with isocyanate.

[0077] This reaction process can be expressed as:

[0078] -RNCO+H2O→-RNHCOOH→-RNH2+ CO2.

[0079] The generated CO2 gas will act as the gas in the bubbles to achieve a heat-insulating effect. The heat released during the reaction can cause the physical foaming agent to volatilize into gas and become part of the foam, thereby enhancing the heat-insulating properties of the foam. In addition, the amine generated by the reaction of water and isocyanate will further react with isocyanate to form a substituted urea bond structure, which can increase the cross-linking density of the material and thus improve the mechanical strength of the foam.

[0080] However, the existing technology has some significant defects due to the presence of CO2 in the bubbles. First, the thermal conductivity of CO2 is relatively high, about 0.0353 W / mK, which is about three times the thermal conductivity of other physical foaming agents. Due to the high thermal conductivity of CO2, when it is used as the main bubble component, the overall thermal conductivity of the foam is also relatively high, affecting the thermal insulation performance of the material.

[0081] Secondly, since water releases heat during the reaction, this heat will cause the physical foaming agent to volatilize, but this process is difficult to control precisely, which can easily lead to an unstable foaming process and affect the uniformity of the foam and the final mechanical properties.

[0082] In order to overcome the above defects, the present invention reduces or avoids the addition of water in the preparation process of polyurethane rigid foam to reduce the generation of CO2 and the release of heat. Specifically, before the material reaction to prepare polyurethane rigid foam, the main material polyether material is dehydrated to control the moisture in the raw material.

[0083] And, instead, low-boiling-point blowing agents are introduced, and the azeotropic point of these blowing agents should be lower than the ambient temperature during the reaction to ensure that they can stably gasify during the reaction and form a uniform foam structure. Since the main reaction of polyurethane rigid foam (RNCO+R'OH→RNHCOOR') itself also generates heat, a group of combined blowing agents needs to be selected to adapt to the gradient of reaction heat changing over time.

[0084] Using low boiling point blowing agents to replace water and CO2 brings many advantages.

[0085] First, low-boiling-point foaming agents usually have lower thermal conductivity, which can significantly improve the thermal insulation effect of the foam.

[0086] Secondly, this method reduces the release of heat during the reaction, avoids the instability of the foaming process caused by temperature changes, and ensures the uniformity of the foam and the stability of the mechanical properties. In addition, the combined foaming agent can adapt to the changes in reaction heat, ensure the continuity and stability of the foaming process, and ultimately improve the overall performance of the foam material.

[0087] In summary, although water plays a key role in the existing polyurethane rigid foam preparation process, the high thermal conductivity and heat release problems it brings cannot be ignored. By reducing the addition of water and introducing low-boiling point foaming agents, these defects can be effectively overcome, the thermal insulation effect and mechanical properties of the foam can be improved, and the application of polyurethane rigid foam in various fields can be further expanded.

[0088] As mentioned above, Polymeric Methylene Diphenyl Diisocyanate (PMDI or Polymeric MDI) is a versatile chemical raw material that can be used to produce polyurethane materials. Polymeric MDI is a polyisocyanate composed of a polymer form of diphenylmethane diisocyanate (MDI). Its chemical structure contains multiple isocyanate groups (-NCO), which makes it highly reactive and versatile.

[0089] In the above, the first low-boiling point foaming agent and the second low-boiling point foaming agent are different low-boiling point foaming agent combinations, wherein in the steps of dividing the first low-boiling point foaming agent into part A and part B, and dividing the second low-boiling point foaming agent into part C and part D, A and B are parts taken from the first low-boiling point foaming agent, and the two parts have the same components, but the amounts are different. Similarly, C and D are parts taken from the second low-boiling point foaming agent, and the components are the same, but the amounts are different.

[0090] As mentioned above, in the present invention, the first low-boiling point foaming agent and the second low-boiling point foaming agent are divided into two parts, and the combined polyether mixture and the polymerized MDI mixture are prepared respectively, and then mixed and reacted to prepare the polyurethane rigid foam. The reason is that:

[0091] (1) Reaction control: Dividing the low-boiling point foaming agent into two parts can better control its reaction process at different stages. The distribution of the foaming agent in the early and late stages affects the formation and uniformity of the foam. By adding it in stages, the foaming process can be made more uniform and controllable, thereby improving the quality of the foam.

[0092] (2) Thermal management: During the formation of rigid polyurethane foam, the reaction releases a large amount of heat. Adding the blowing agent in stages helps manage the heat of the reaction, making the foaming process more stable and avoiding local overheating or uneven cooling. This thermal management can avoid defects in the foam structure and improve the performance of the final product.

[0093] (3) Optimization of physical properties: Different foaming agents play different roles under different reaction conditions. Adding the foaming agent in multiple portions can optimize its physical properties at each stage of foam formation, ensuring that the foam has the best properties such as density, hardness and thermal conductivity.

[0094] (4) Reduce volatility loss: Low-boiling-point blowing agents are easy to volatilize. If all of them are added at the beginning of the reaction, it may lead to large volatility losses. Adding them in stages can reduce volatility losses, improve the utilization efficiency of the blowing agent, and ensure the uniformity and performance stability of the final foam.

[0095] Its advantages are:

[0096] (1) Improving foam uniformity: By adding the foaming agent in stages, it is possible to ensure that the bubbles are evenly distributed in the foam structure, reduce the generation of large bubbles and voids, and thus improve the uniformity and structural stability of the foam.

[0097] (2) Enhanced mechanical properties: This method can optimize the cross-linked structure of the foam and improve the mechanical properties of the material, such as compressive strength and tensile strength. The uniform foaming process makes the internal structure of the foam more dense and stable, enhancing the strength of the overall material.

[0098] (3) Improved thermal insulation effect: The optimized use of low-boiling point foaming agents at different stages can make the bubbles inside the foam more stable and uniform, reduce the heat conduction path within the bubbles, and thus improve the thermal insulation performance of the foam.

[0099] (4) Reduce production costs: Adding the foaming agent in stages can improve its utilization efficiency and reduce waste, thereby reducing production costs. In addition, this method can reduce defects and scrap rates and improve production efficiency.

[0100] (5) Better process flexibility: This method allows the type and proportion of foaming agent to be adjusted at different stages, making the production process more flexible and controllable, and better adapted to different production needs and product specifications.

[0101] In summary, the preparation method of dividing the low boiling point foaming agent into two parts and adding them to the combined polyether mixture and the polymerized MDI mixture respectively, and then conducting a mixing reaction, can provide a more flexible and efficient production process by precisely controlling the reaction process, optimizing thermal management, improving foam uniformity and mechanical properties, improving thermal insulation effects, and reducing production costs.

[0102] In summary, the present invention dehydrates the polyether material to eliminate the effects of heat and carbon dioxide generated by the addition of water, and adds a combination of multiple low-boiling point foaming agents, thereby maintaining the toughness of the foam and greatly reducing the thermal conductivity of the material.

[0103] In addition, the raw materials of conventional polyurethane rigid foam materials have a short shelf life and may delaminate after long-term storage, which is usually caused by the following factors:

[0104] First, the raw materials of polyurethane rigid foam materials usually contain a variety of chemical components, which may undergo slow chemical reactions during storage, resulting in changes in the properties of the material and causing stratification; secondly, the chemical properties of different components in the raw materials may be incompatible. Over time, this incompatibility will cause separation between the components and form stratification.

[0105] In the present application embodiment, in the preparation process of the polyurethane rigid foam material, the long-term storage of the intermediate raw materials, i.e., the combined polyether mixture and the polymerized MDI mixture without stratification, mainly depends on the following aspects:

[0106] First, polyether materials need to be dehydrated to ensure that their water content is controlled at an extremely low level (no more than 0.01%). Strict control of water content can prevent hydrolysis from occurring, thereby extending the stability and shelf life of the material.

[0107] Secondly, the formulation design of the combined polyether mixture and the polymeric MDI mixture includes preservatives such as isotridecyl alcohol and cocamide. Preservatives have an antioxidant effect and can slow down or prevent the oxidation reaction of the components in the raw materials and prolong the stability of the raw materials. Preservatives can improve the physical compatibility between different components in the raw materials and reduce the stratification caused by differences in physical properties. Preservatives can stabilize the chemical composition of the raw materials to prevent them from decomposing or polymerizing during storage. Preservatives can reduce the impact of environmental factors (such as temperature and humidity) on the stability of the raw materials and reduce the risk of stratification caused by environmental factors. In short, these preservatives can slow down the aging process of the materials and improve their chemical stability, thereby extending the shelf life.

[0108] During the preparation process, the first and second low boiling point blowing agents are added to the combined polyether mixture and the polymerized MDI mixture in multiple portions. This step-by-step addition method helps control the reaction rate and uniformity of the reaction and reduces the possibility of stratification.

[0109] During the dehydration process, strict control of temperature and vacuum degree helps to remove moisture and low-boiling point components in polyether substances, further improving the stability of the material.

[0110] The above measures can ensure that the intermediate raw materials of polyurethane rigid foam materials remain stable and do not delaminate during the 6-month shelf life. These measures work together to form a stable chemical environment, allowing the intermediate raw materials to maintain the consistency of their physical and chemical properties for a longer period of time.

[0111] Furthermore, in the combined polyether mixture, the weight proportions of the various raw materials are respectively:

[0112] Polyether substances after dehydration treatment 74-95.5;

[0113] Catalytic system mixture 1-2;

[0114] 0-5% of the A portion of the first low boiling point blowing agent;

[0115] Part C 1-15 of the second low boiling point blowing agent;

[0116] Tertiary amine catalyst 0.5-1;

[0117] Preservative 2-3.

[0118] Furthermore, in the polymeric MDI mixture, the weight proportions of the various raw materials are respectively:

[0119] Polymeric MDI 80-100;

[0120] 0-5% of the B portion of the first low boiling point blowing agent;

[0121] The second low boiling point blowing agent contains 0-15 parts of D.

[0122] Further, the weight percentages of A, B, C and D are 15-20 in total;

[0123] Furthermore, in the mixing reaction of the combined polyether mixture and the polymeric MDI mixture, the weight ratio of the polymeric MDI mixture to the combined polyether mixture is 1.2:1.

[0124] As described above, when preparing the polymerized MDI mixture, adjustments can be made based on the addition of the first low-boiling point foaming agent and the second low-boiling point foaming agent in the combined polyether mixture. The first low-boiling point foaming agent and the second low-boiling point foaming agent may not be added to the polymerized MDI mixture, or corresponding amounts of the first low-boiling point foaming agent and the second low-boiling point foaming agent may be added to the polymerized MDI mixture.

[0125] In the above, the weight fractions of A, B, C and D are always 15-20; here, it means that the sum of the weight fractions of parts A and C in the combined polyether mixture and the weight fractions of part BD in the polymerized MDI mixture is in the range of 15-20. This can be specifically expressed by the following expression:

[0126] (A+C)+(B+D)=15-20.

[0127] For example, in terms of weight parts, the total is 19, in the combined polyether mixture, part A of the first low-boiling point foaming agent is 3, and part C of the second low-boiling point foaming agent is 8; then in the polymerized MDI mixture, part B of the first low-boiling point foaming agent is 7, and part D of the second low-boiling point foaming agent is 1.

[0128] In the above-mentioned method for preparing polyurethane rigid foam material, the reason for limiting the weight percentage of A, B, C and D to 15-20 is related to the influence of the amount of foaming agent on the performance of the final product. Here, A, B, C and D represent different parts of low-boiling foaming agents, which play a key role in the production of polyurethane rigid foam material. Specifically, this control is related to the following aspects:

[0129] (1) Foaming efficiency and density control: The total amount of foaming agent affects the foaming efficiency of the material and the final cell structure. Controlling it within 15-20 parts by weight helps maintain a certain foaming rate, thereby obtaining the desired density and hardness. Too much or too little foaming agent may result in uneven cells or material density that does not meet the requirements.

[0130] (2) Physical and mechanical properties: The physical properties of polyurethane rigid foam, such as thermal conductivity, strength and toughness, are closely related to the size and distribution of cells. By precisely controlling the amount of foaming agent, these cell characteristics can be adjusted, thereby optimizing the overall performance of the material.

[0131] (3) Balance of chemical reaction: In the synthesis process of polyurethane, the amount of foaming agent used will also affect the completeness and reaction rate of the reaction. The appropriate amount of foaming agent helps to achieve a good balance of chemical reactions and ensure the chemical stability and performance consistency of the material.

[0132] Cell structure (size, distribution and closure) is a key factor in determining the thermal conductivity of rigid polyurethane foam. Generally, a more uniform and smaller closed cell structure can reduce the thermal conductivity of the material because gases transfer heat less efficiently than solids. Therefore, by controlling the total amount of blowing agent, the cell structure can be indirectly controlled, thereby optimizing the thermal conductivity of the material.

[0133] In general, limiting the weight percentages of A, B, C and D within a specific range is to ensure that the material meets the comprehensive performance requirements of the design, including mechanical strength, thermal conductivity, etc. This control is based on a deep understanding of the factors affecting the performance of polyurethane rigid foam materials and actual application needs.

[0134] As mentioned above, in the preparation process of the polyurethane rigid foam material, the weight ratio of the polymerized MDI mixture to the combined polyether mixture is determined to be 1.2:1, because this ratio directly affects the efficiency of the polymerization reaction and the quality of the product.

[0135] First, polymeric MDI (toluene diisocyanate) and polyethers are the main chemical reaction components for making polyurethane. Polyethers contain multiple hydroxyl groups (OH), while polymeric MDI contains multiple isocyanate groups (NCO). The correct ratio of these two components is key to ensure that the reaction between hydroxyl and isocyanate groups is sufficient. Too much MDI may result in unreacted NCO groups remaining, while too little MDI may result in some hydroxyl groups failing to react, both of which will affect the performance of the material.

[0136] Secondly, the ratio of polymeric MDI to polyether not only determines the crosslinking density of the polymer network, but also affects the microstructure of the foam. The appropriate NCO / OH ratio helps to form a stable closed-cell structure, which is crucial to improving the thermal insulation performance, mechanical strength and water resistance of the material.

[0137] Thirdly, the appropriate chemical reaction ratio can optimize the density, hardness, elasticity and durability of rigid polyurethane foam. Precisely controlling the ratio of polymerized MDI and polyether during the preparation process helps to produce high-performance polyurethane materials that meet specific application requirements.

[0138] Furthermore, the dehydration treatment is performed by heating and vacuum decompression drying;

[0139] Furthermore, the vacuum degree of the dehydration treatment is 0.02 MPA -0.04 MPA;

[0140] Furthermore, the temperature of the dehydration treatment is 60°C-80°C;

[0141] Furthermore, the dehydration time of the dehydration treatment is 60 min-90 min;

[0142] Furthermore, the standard of the dehydration treatment is: controlling the water content of the polyether substance to be no greater than 0.01.

[0143] The purpose of dehydration by heating and vacuuming is to efficiently and thoroughly remove the water in polyether materials to ensure that the water content is controlled below 0.01% during the reaction. This method combines two physical means, heating and vacuuming, and can achieve efficient dehydration at a relatively low temperature.

[0144] In a vacuum environment, the boiling point of water will be significantly reduced. Under normal pressure, the boiling point of water is 100°C, but under a vacuum of 0.02-0.04 MPa, the boiling point of water can be reduced to around 60-80°C. This means that water can be evaporated at a lower temperature, thereby effectively removing water from polyether substances.

[0145] Polyethers and other reaction components may be sensitive to high temperatures, and prolonged exposure to high temperatures may lead to degradation or other side reactions. By dehydrating at low temperatures, the impact on heat-sensitive substances can be reduced, ensuring the stability of the material and the effectiveness of the reaction.

[0146] Heating can increase the evaporation rate of water, while the pressure reduction under vacuum conditions further promotes the evaporation of water. This combined method can achieve efficient dehydration in a shorter time and ensure the thoroughness of the dehydration process.

[0147] Under vacuum conditions, the oxygen content is extremely low, which can effectively prevent some easily oxidizable components from undergoing oxidation reactions and maintain the chemical stability of the material.

[0148] Efficient dehydration: The combination of heating and vacuum can quickly reduce the moisture content in the material, ensuring that the moisture content is controlled below 0.01% within 60-90 minutes, greatly improving the dehydration efficiency.

[0149] Low temperature treatment: Dehydration at a low temperature of 60-80℃ can not only effectively remove moisture, but also avoid thermal damage and side reactions to the material caused by high temperature, and protect the integrity of polyether substances and other components.

[0150] Energy saving and environmental protection: Compared with the method of long-term heating and dehydration at high temperature, vacuum heating and dehydration can achieve the same effect at a lower temperature, reduce energy consumption, and improve the energy utilization efficiency of the production process.

[0151] Stable process: The vacuum dehydration process can continuously monitor and adjust the vacuum degree and temperature to ensure the stability and controllability of the dehydration process and the quality consistency of the final product.

[0152] Protect material properties: Dehydration treatment under low temperature and low oxygen conditions can avoid degradation and oxidation reactions of heat-sensitive materials, ensuring the purity of reaction raw materials and the effectiveness of the reaction.

[0153] In summary, the purpose of using the heating and vacuuming method for dehydration is to efficiently and thoroughly remove the water in polyether materials at low temperatures, while avoiding damage and side reactions to the materials caused by high temperatures, ensuring the stability of the production process and the consistency of product quality. This method not only improves the dehydration efficiency, but also protects the chemical properties of the materials, and has significant technical and economic advantages.

[0154] Furthermore, the polyether substance includes:

[0155] OTDA polyether, polyester, sorbitol polyether, silicone oil and amine catalyst;

[0156] Furthermore, the polyether material includes the following components in parts by weight:

[0157] OTDA polyether 56-77.5;

[0158] Polyester 10-20;

[0159] Sorbitol polyether 10-20;

[0160] Silicone oil 1.5-2;

[0161] Amine catalyst 1-2.

[0162] Further, the catalyst system mixture comprises:

[0163] Organotins, organobismuths, and perfluoroolefins;

[0164] Furthermore, the catalyst system mixture includes the following components in parts by weight:

[0165] Organic tin 5-40;

[0166] Organic bismuth 5-40;

[0167] Perfluoroolefin 20-90.

[0168] It should be noted that the low-boiling point blowing agent used in the present invention is a blowing agent with a relatively low boiling point, some of which are lower than 0°C or even around -30°C. It will quickly vaporize at room temperature during the mixed reaction and will not enter the bubbles to cause mass loss. The current mass loss is about 3-8% of the total mass of the isocyanate and the combined polyether.

[0169] Therefore, the reaction nucleation must be carried out quickly, the milky time must be controlled within 1-8 seconds, and at the same time, heat must be provided from the outside to achieve this effect.

[0170] To make the physical foaming agent easier to nucleate into bubbles, heat is provided from the outside, such as microwave technology. A faster milky reaction is introduced, so the catalytic system is the key, and organic tin and organic bismuth are introduced to promote the reaction. In order to make the bubbles finer and the pores smaller, perfluoroolefins are introduced for better nucleation, so that the gas volatilization loss is within the range of 0.5%-1% of the comprehensive mass.

[0171] In order to accelerate the milky time of foaming, nucleate as soon as possible and reduce gas escape, a catalytic system mixture was introduced, which is a mixture of organic tin, organic bismuth and perfluoroolefin, so that the total mass loss is controlled from the volatilization loss of about 3-8% to 0.5%-1%.

[0172] Furthermore, the first low-boiling point blowing agent is selected from at least one of pentane, methyl formate, HFC-245fa, LBA, R600, R600a, R152a, R134a, R1234yf, opteon 1100 / 1150, HCFO-1224yd, HCFO-1234ze, HCFO-1243zf, HCFO-1233xf and trifluoropropylene.

[0173] Further, the second low boiling point blowing agent includes neopentane, tetramethylsilane and hexafluoropropylene;

[0174] Furthermore, the second low-boiling point foaming agent includes the following components in parts by weight:

[0175] Neopentane 5-20;

[0176] Tetramethylsilane 5-50;

[0177] Hexafluoropropylene 60-90.

[0178] In order to ensure that downstream products do not break bubbles, the pressure in the pressure pipeline is stable and effective during production, and the gas in the bubbles does not overflow over a long period of time, causing the thermal conductivity to decay. A mixed foaming agent, a combination of neopentane, tetramethylsilane and hexafluoropropylene, was introduced to control the thermal conductivity decay from the original maximum of 8% in 4 months to less than 2%.

[0179] This combination is adopted by comprehensively considering the boiling points, saturated vapor pressures and gas phase thermal conductivity of the three foaming agents, and at the same time, the hot body surface tension of the mixture is low in the eutectic state.

[0180] Furthermore, the tertiary amine catalyst is TOYOCAT-SX60.

[0181] As mentioned above, in order to improve the toughness of the cell wall and to ensure stable and progressive cell formation, so that the cells are not squeezed, the cell structure is uniform, and the cells are not broken when the pressure difference at altitude is large, TOYOCAT-SX60 tertiary amine catalyst is introduced in the present invention.

[0182] As mentioned above, TOYOCAT-SX60 is a tertiary amine catalyst, mainly used in the production of polyurethane foam. Its function is to accelerate the reaction in the synthesis process of polyurethane, improve production efficiency and foam performance.

[0183] Tertiary amine catalysts can significantly accelerate the reaction of isocyanates and polyols in the polyurethane foam formation process, thereby shortening the reaction time. By accelerating the reaction, the catalyst can help form a more uniform foam structure and improve the physical properties of the foam, such as compressive strength and cell uniformity. The catalyst can also help control the temperature changes of the reaction, making the reaction more stable.

[0184] As a highly efficient catalyst, TOYOCAT-SX60 can significantly increase the reaction rate and reduce the possibility of gas escape, thereby reducing the quality loss of the foam. It shows good stability under high temperature and high pressure environments and is suitable for various industrial production conditions. The catalyst helps to form a fine and uniform cell structure, improving the thermal insulation performance and mechanical strength of the foam.

[0185] Using TOYOCAT-SX60 can help reduce gas escape during the foam molding process, improve the overall density and thermal conductivity of the foam. It can enhance the toughness of the foam wall and reduce the risk of foam rupture at high altitudes or in environments with large pressure differences. By improving the stability of the foam, the catalyst helps to extend the storage time of the foam and reduce the change in thermal conductivity.

[0186] In summary, TOYOCAT-SX60 is an effective tertiary amine catalyst that plays an important role in improving the performance and production efficiency of polyurethane rigid foam. It optimizes the thermal conductivity and storage stability of the foam by accelerating the reaction, improving the toughness of the foam wall and reducing gas overflow.

[0187] Further, the preservative includes: isotridecyl alcohol and cocamide;

[0188] As mentioned above, in order to avoid the stratification of raw materials in the combined polyether mixture during long-term storage (storage period exceeding 3 months), a mixture of isotridecyl alcohol (20%-50%) + cocamide (50%-80%) is introduced as a preservative in the embodiment of the present application, which will make the polyether more soluble and prevent stratification within 6 months of storage.

[0189] Furthermore, the preservative includes the following components in parts by weight:

[0190] Isotridecyl alcohol 20-50;

[0191] Cocamide 50-80.

[0192] As mentioned above, Isononyl Alcohol is a saturated fatty alcohol that is used as a component of lubricants, solvents and surfactants. Its chemical structure is an alkyl chain consisting of nine carbon atoms with a hydroxyl (-OH) group at the end.

[0193] As mentioned above, cocamide is a compound derived from coconut oil and belongs to the class of fatty acid amides. It is commonly used as a surfactant, lubricant and thickener.

[0194] Furthermore, the mixing reaction of the combined polyether mixture and the polymeric MDI mixture further comprises:

[0195] Perform microwave heating during the reaction;

[0196] Furthermore, the microwave heating treatment time is: heating to 30-200 seconds after the reaction starts;

[0197] Furthermore, the frequency of the microwave heating treatment is: 1.5 GHz -3.2 GHz.

[0198] As mentioned above, in order to ensure the heat supply during the reaction, microwave technology needs to be added for initial heating. The heating time is from the start of the reaction until it reaches 30-200 seconds, and the heating microwave frequency is 1.5-3.2 GHz.

[0199] It should be noted that in the preparation process of polyurethane rigid foam, microwave heating treatment has many effects:

[0200] (1) Ensure rapid initial heating: In the initial reaction stage of polyurethane foam production, reaction rate and temperature control are crucial. Microwave heating can quickly provide the required heat in a short time (30-200 seconds), ensuring that the reaction temperature quickly reaches the required level, thereby promoting the smooth progress of the reaction.

[0201] (2) Provide uniform heat distribution: Microwave heating can effectively penetrate into the material and evenly distribute heat through the frequency of 1.5-3.2 GHz. This helps to avoid local overheating or overcooling and ensures uniform temperature distribution of polyurethane foam during the initial heating process, thereby obtaining uniform foam structure and quality.

[0202] (3) Precise control of heating time: The heating time is set between 30 and 200 seconds. Microwave heating can precisely control the heating process within this time period to ensure that the reaction is carried out within the optimal temperature range. This precise control helps improve product consistency and quality and avoids quality problems caused by insufficient or excessive heating.

[0203] (4) Improve production efficiency: Microwave heating can quickly provide the required heat and significantly shorten the initial heating time. This not only improves production efficiency, but also reduces energy consumption, which is more energy-efficient than traditional heating methods. Rapid initial heating also helps to speed up the overall production cycle and increase output.

[0204] (5) Adapt to different reaction conditions: By adjusting the microwave frequency (1.5-3.2 GHz) and heating time (30-200 seconds), it can flexibly adapt to different reaction conditions and process requirements. Microwaves of different frequencies can provide the best heating effect for different materials and reaction systems, ensuring the flexibility and adaptability of the process.

[0205] (6) Improving material properties: Rapid and uniform initial heating can promote the sufficient mixing and reaction of polyurethane precursors with additives (such as isoisotridecanol and coconut oil amide), improving the mechanical properties and physical characteristics of the foam material. Uniform heating can also reduce bubble defects and enhance the uniformity and stability of the foam.

[0206] In summary, by using microwave technology for initial heating, the heat supply during the reaction can be effectively ensured, with rapid and uniform heating within 30 - 200 seconds and a frequency range of 1.5 - 3.2 GHz. This not only improves production efficiency, ensures the consistency of product quality, but also enables flexible adjustment according to different process requirements, ultimately improving the performance and quality of polyurethane foam.

[0207] In addition, the present invention also provides a rigid polyurethane foam material prepared by the preparation method of the rigid polyurethane foam material as described above.

[0208] The present invention will be further illustrated by specific examples below. However, it should be understood that these examples are only for more detailed illustration and should not be construed as limiting the present invention in any form.

[0209] Table 1. Different ratios of mixture raw materials

[0210]

[0211] Table 2. Different ratios of combined polyether mixtures in the examples

[0212]

[0213] Table 3. Different ratios of polymeric MDI mixtures in the examples

[0214]

[0215] In the above tables, "Ex." represents an example, such as "Ex. 1" which is Example 1; "Comp." represents a comparative example, such as "Comp. 1" which is Comparative Example 1, "Form." represents a formulation, and "Form. 1" is "Formulation 1" and so on.

[0216] Example 1:

[0217] In this example, based on the ratios in Table 2 and Table 3, a rigid polyurethane foam product was prepared by the following method. Among them, the configuration of polyether substances, catalytic system mixture, second low-boiling foaming agent, and preservative refers to Form. 1 in Table 1.

[0218] Preparation method:

[0219] (1) Dehydrating the polyether material; the vacuum degree of the dehydration treatment is 0.02 MPA; the temperature is 60° C.; and the dehydration time is 60 min;

[0220] (2) preparing a polyether substance, a catalyst system mixture, a first low-boiling point blowing agent (pentane), a second low-boiling point blowing agent, a tertiary amine catalyst, a quality assurance agent and polymeric MDI respectively, and dividing the first low-boiling point blowing agent into part A and part B, and dividing the second low-boiling point blowing agent into part C and part D;

[0221] (3) preparing a combined polyether mixture using the dehydrated polyether substance, the catalyst system mixture, part A of the first low-boiling point foaming agent, part C of the second low-boiling point foaming agent, the tertiary amine catalyst and the quality assurance agent;

[0222] (4) preparing a polymeric MDI mixture using the polymeric MDI, part B of the first low-boiling point foaming agent and part D of the second low-boiling point foaming agent;

[0223] (5) The combined polyether mixture and the polymeric MDI mixture are mixed for reaction, wherein the weight percentages of A, B, C and D are required to be 20 in total; the weight percentage of the polymeric MDI mixture is 1.2 times that of the combined polyether mixture; microwave heating is performed during the reaction to obtain the polyurethane rigid foam material; the microwave heating time is: heating to 30 seconds after the reaction starts; the frequency is: 1.5 GHz.

[0224] Embodiment 2:

[0225] In this embodiment, a polyurethane rigid foam product is prepared based on the ratios in Table 2 and Table 3. The configurations of the polyether substance, the catalyst system mixture, the second low boiling point foaming agent and the quality assurance agent refer to the configuration 2 in Table 1.

[0226] Preparation method:

[0227] It is basically the same as Example 1, except that:

[0228] The first low boiling point foaming agent is methyl formate;

[0229] The vacuum degree of the dehydration treatment is 0.03 MPA; the temperature is 70°C; the dehydration time is 75 min;

[0230] The microwave heating treatment time in step (5) is 100 seconds after the reaction starts; the frequency is 2.5 GHz.

[0231] Embodiment 3:

[0232] In this embodiment, a polyurethane rigid foam product is prepared based on the ratios in Table 2 and Table 3. The configurations of the polyether substance, the catalyst system mixture, the second low boiling point foaming agent and the quality assurance agent refer to the configuration 3 in Table 1.

[0233] Preparation method:

[0234] It is basically the same as Example 1, except that:

[0235] The first low boiling point blowing agent is HFC-245fa;

[0236] The vacuum degree of the dehydration treatment is 0.04 MPA; the temperature is 80°C; and the dehydration time is 90 min;

[0237] The microwave heating treatment in step (5) is carried out for 200 seconds after the reaction starts; the frequency is 3.2 GHz.

[0238] Embodiment 4:

[0239] In this embodiment, a polyurethane rigid foam product is prepared based on the ratios in Table 2 and Table 3. The configurations of the polyether substance, the catalyst system mixture, the second low boiling point foaming agent and the quality assurance agent refer to the configuration 1 in Table 1.

[0240] Preparation method:

[0241] It is basically the same as Example 1, except that the first low-boiling point foaming agent is LBA.

[0242] The vacuum degree of the dehydration treatment is 0.02 MPA; the temperature is 80°C; and the dehydration time is 90 min;

[0243] The microwave heating treatment time in step (5) is 100 seconds after the reaction starts; the frequency is 2.5 GHz.

[0244] Embodiment 5:

[0245] In this embodiment, four groups of samples were prepared using the formula in Example 3, and the samples were prepared at different altitudes, namely: 5-1: 23 meters, 5-2: 560 meters, 5-3: 1570 meters, and 5-4: 2320 meters. Based on the ratios in Tables 2 and 3, polyurethane rigid foam products were prepared. The configurations of the polyether substance, the catalytic system mixture, the second low-boiling point foaming agent, and the quality-preserving agent refer to the configuration 1 in Table 1.

[0246] Preparation method: Same as Example 1.

[0247] Comparative Example 1:

[0248] This comparative example is basically the same as Example 1, except that in step (3), no preservative is added.

[0249] Comparative Example 2:

[0250] This comparative example is basically the same as Example 1, except that the step “(1) dehydrating the polyether substance” is not performed.

[0251] Comparative Example 3:

[0252] This comparative example is basically the same as Example 1, except that in the step "(1) the polyether material is subjected to a dehydration treatment, the vacuum degree of the dehydration treatment is 0.1 MPa; the temperature is 60° C.; and the dehydration time is 60 min".

[0253] Comparative Example 4:

[0254] This comparative example is basically the same as Example 1, except that, when the combined polyether mixture and the polymeric MDI mixture are mixed and reacted in step (5), "microwave heating treatment during the reaction" is not performed to obtain the polyurethane rigid foam material.

[0255] Comparative Example 5:

[0256] This comparative example is basically the same as Example 1, except that, in step (5), when the combined polyether mixture and the polymerized MDI mixture are mixed and reacted, microwave heating treatment is performed during the reaction to obtain the polyurethane rigid foam material; the microwave heating treatment time is: heating to 10 seconds after the reaction starts; the frequency is: 1.5 GHz.

[0257] Comparative Example 6:

[0258] This comparative example is basically the same as Example 1, except that, in step (5), when the combined polyether mixture and the polymeric MDI mixture are mixed and reacted, microwave heating treatment is performed during the reaction to obtain the polyurethane rigid foam material; the microwave heating treatment time is: heating to 30 seconds after the reaction starts; the frequency is: 0.5 GHz.

[0259] Comparative Example 7:

[0260] This comparative example is basically the same as Example 1, except that no organotin and organobismuth are added to the catalyst system mixture in step (2).

[0261] Comparative Example 8:

[0262] This comparative example is basically the same as Example 1, except that no perfluoroolefin is added to the catalyst system mixture in step (2).

[0263] Comparative Example 9:

[0264] This comparative example is basically the same as Example 1, except that no perfluoroolefin is added to the catalyst system mixture in step (2).

[0265] Comparative Example 9:

[0266] This comparative example is basically the same as Example 1, except that TOYOCAT-SX60 is not added to the catalyst system mixture in step (2).

[0267] Comparative Example 10:

[0268] In this comparative example, four groups of samples were prepared at different altitudes, namely: 10-1: 23 meters, 10-2: 560 meters, 10-3: 1570 meters, and 10-4: 2320 meters, the difference being that the second low-boiling point foaming agent was not added.

[0269] Comparative Example 11:

[0270] In this comparative example, four groups of samples were prepared at different altitudes, namely: 11-1: 23 meters, 11-2: 560 meters, 11-3: 1570 meters, and 11-4: 2320 meters, the difference being that no tertiary amine catalyst TOYOCAT-SX60 was added.

[0271] 1. Comparative experiment 1: Long-term placement test of combined polyether mixture

[0272] (1) Experimental method: The combined polyether mixtures prepared in Examples 1-4 and Comparative Example 1 were sealed, and then placed for different periods of time and observed.

[0273] (2) Result analysis: The specific results are shown in the following table.

[0274] Table 4. Storage time of the combined polyether mixture of the embodiments and comparative examples

[0275]

[0276] In comparative experiment 1, the long-term storage effect of the combined polyether mixture with and without the addition of a preservative was observed. From the experimental results, the addition of the preservative significantly improved the long-term stability of the mixture and prevented stratification and turbidity.

[0277] It should be noted that 30 days is taken as a measurement month, and the inspection is conducted at 30 days (1 month), 60 days (2 months), 90 days (3 months), 120 days (4 months), 150 days (5 months), 180 days (6 months), and 210 days (7 months). In the table, "√" represents that the combined polyether mixture is not stratified, which is consistent with the initial state; "×" represents that the combined polyether mixture is stratified and turbid.

[0278] Examples 1-4: These samples were all added with a preservative (mixture of isotridecyl alcohol and cocamide), showing excellent stability. Even after being stored for 7 months, the mixture remained non-stratified and non-turbid. This shows that the preservative effectively maintains the uniformity and stability of the combined polyether mixture.

[0279] Comparative Example 1: The sample without a preservative began to show stratification and turbidity after 3 months of storage, and this phenomenon became more serious as time went on. This shows that in the absence of a preservative, the components in the combined polyether mixture have poor compatibility and are prone to chemical or physical changes over time, leading to stratification.

[0280] It should be noted that the mixture of isotridecyl alcohol and cocamide maintains the homogeneity of the mixture by improving the compatibility of the different components in the mixture. This compatibility is achieved by adjusting the balance of polar and non-polar in the mixture, thereby preventing the separation of different components due to incompatibility.

[0281] Preservatives also have the function of inhibiting or slowing down chemical reactions, such as oxidation or hydrolysis, which may cause changes in the properties of the polyether components and thus induce separation. By providing a certain viscosity and surface tension adjustment, preservatives help maintain the physical stability of the mixture and avoid sedimentation or floating of components due to external factors such as gravity.

[0282] Experiments show that the use of a preservative is a key factor in ensuring the long-term stable storage of a polyether mixture. Without a preservative, the polyether mixture is prone to stratification and turbidity in a short period of time, affecting its quality and subsequent use. However, a reasonable ratio of preservatives can significantly improve the storage stability of the mixture, which is of great significance for reducing production costs and improving product quality.

[0283] 2. Comparative experiment 2: Effect of raw material dehydration on thermal conductivity of polyurethane rigid foam material

[0284] In this comparative experiment, the effect of raw material dehydration on the thermal conductivity of polyurethane rigid foam materials was investigated.

[0285] Experimental methods:

[0286] The thermal conductivity of the materials prepared in the above Examples 1-4 and Comparative Examples 2-3 was tested.

[0287] Result analysis: The results are shown in the following table.

[0288] Table 5. Thermal conductivity results of the embodiments and comparative examples

[0289]

[0290] Refer to Table 5 and Figure 2 In this comparative experiment 2, the effect of raw material dehydration on the thermal conductivity of polyurethane rigid foam was investigated, and the experimental data clearly showed the effect of moisture content on thermal conductivity. The dehydration of polyether materials is a key step, because moisture will react with isocyanate in the polyurethane reaction to generate carbon dioxide and ammonia, which not only affects the chemical structure of the foam, but also may cause uneven internal structure of the foam.

[0291] Examples 1-4: The moisture content of these samples was controlled between 0.007 and 0.005, and the corresponding thermal conductivity was also maintained at a low level (0.0133 to 0.0137 W / m·K). Lower moisture content means less carbon dioxide is generated during the polymerization reaction, resulting in a more uniform and closed foam structure, which helps to reduce the transfer of heat energy through the material.

[0292] Comparative Example 2: No dehydration was performed, and the moisture content was as high as 0.132, resulting in a significant increase in thermal conductivity to 0.0189 W / m·K. This indicates that the high moisture content resulted in a large amount of carbon dioxide generation, which may cause the foam structure to break or become uneven, thereby increasing the thermal conductivity of the material.

[0293] Comparative Example 3: Despite the reduced pressure drying treatment, the vacuum degree was insufficient and the moisture content was still higher than 0.01 (reaching 0.033), resulting in a thermal conductivity of 0.0166 w / m·k. This indicates that the dehydration treatment was not effective enough and failed to meet the ideal dehydration standard.

[0294] It should be noted that moisture reacts with isocyanate: During the polyurethane preparation process, the carbon dioxide generated by the reaction of moisture with isocyanate will act as an internal foaming agent, which will form additional bubbles in the material. If there is too much moisture, these bubbles may be too large or uneven, destroying the closed structure of the foam and resulting in higher thermal conductivity.

[0295] The ideal polyurethane rigid foam should have a uniform and closed micro-bubble structure. Controlling the moisture content is the key to achieving this structure, because uneven or overly large bubbles will increase the voids inside the material, thereby increasing the heat transfer efficiency.

[0296] Effective dehydration treatment can ensure that the moisture content in polyether materials is reduced to a minimum, thereby optimizing the reaction conditions and the consistency of the foam structure and reducing the thermal conductivity.

[0297] The results show that in the present technology, the polyether material is dehydrated to eliminate the effect of heat and carbon dioxide generated by the addition of water, and the thermal conductivity of the material is reduced compared with the material not dehydrated in Comparative Example 2. In Comparative Example 3, the vacuum degree is insufficient. Although the reduced pressure drying treatment is also carried out, the water content is still greater than 0.01, reaching 0.033, and the thermal conductivity also reaches 0.0166w / m·k, indicating that the water content in the material can be efficiently removed under a vacuum degree of 0.02 MPA-0.04MPA, so as to produce a qualified polyurethane rigid foam material.

[0298] In conclusion, through these experimental results, it can be clearly seen that effective raw material dehydration treatment is crucial to controlling the thermal conductivity of polyurethane rigid foam materials. Controlling the moisture content not only affects the internal chemical reaction of the material, but is also directly related to the thermal insulation performance of the final product. Therefore, in actual production, the moisture content of the raw materials should be strictly monitored and controlled to ensure the efficiency and effect of the dehydration process in order to prepare polyurethane rigid foam materials with superior performance.

[0299] 3. Comparative experiment 3: Microwave heating treatment investigation

[0300] In this comparative experiment, the effect of microwave heating treatment on the thermal conductivity of the material was investigated.

[0301] (1) Experimental methods:

[0302] The thermal conductivity of the materials prepared in the above Examples 1-4 and Comparative Examples 4-6 was tested.

[0303] (2) Result analysis: The results are shown in the following table.

[0304] Table 6. Thermal conductivity results of the embodiments and comparative examples

[0305]

[0306] The results show that microwave heating has a significant impact on the preparation process of polyurethane rigid foam materials, especially in ensuring the thermal conductivity and production efficiency of the materials. Through this comparative experimental result, we can deeply analyze the specific effects of microwave heating parameters (such as heating time and frequency) on material properties.

[0307] Examples 1-4 used microwave heating technology, and the thermal conductivity results were relatively low (0.0133 to 0.0138 w / m·k), showing good thermal insulation performance. In these examples, microwave heating with a frequency range of 1.5 to 3.2 GHz and a heating time of 30 to 200 seconds were used. These parameters can help achieve rapid and uniform material curing, thereby optimizing the bubble structure, improving the uniformity and airtightness of the foam, and effectively reducing the thermal conductivity of the material.

[0308] In Comparative Examples 4-6, the thermal conductivity is relatively high (0.0175 to 0.0186 w / m·k), indicating that in these samples, microwave heating treatment failed to achieve the same effect as in the examples. Specifically:

[0309] In Comparative Example 5, the microwave heating time is relatively short, which results in that the chemical reaction in the material cannot be completed uniformly in the entire mixture, thereby affecting the uniformity and airtightness of the foam, and ultimately resulting in a higher thermal conductivity.

[0310] The microwave frequency in Comparative Example 6 is set to only 0.5 GHz, which is much lower than the frequency in the embodiment. The lower frequency leads to insufficient energy transfer, which cannot effectively promote uniform heating and curing of the material, and also affects the quality of the foam structure.

[0311] It should be noted that microwave heating provides an effective internal heating method that can quickly increase the temperature inside the material, helping chemical reactions and the solidification of the material. Appropriate heating time and frequency are critical to the following aspects:

[0312] Chemical reaction rate: Appropriate microwave heating can accelerate the polymerization reaction, help complete the cross-linking reaction in a shorter time, and form a stable polyurethane network structure.

[0313] Bubble formation and stability: Uniform heating helps control bubble generation and growth, promoting the formation of smaller and evenly distributed bubbles, which directly affects the thermal conductivity of the material.

[0314] Uniform curing of materials: Microwave heating can ensure uniform heating of the interior and surface of the material, avoiding the problems of surface overheating and insufficient internal reaction that may be caused by traditional heating methods.

[0315] In summary, the optimal use of microwave heating (including the appropriate setting of frequency and time) is a key factor in improving the performance of polyurethane rigid foam materials. The lower thermal conductivity in Examples 1-4 and the higher thermal conductivity in Comparative Examples 5-6 clearly demonstrate the influence of microwave heating parameters on material properties. In actual production, these parameters should be carefully controlled to ensure that the material meets the expected performance standards.

[0316] 4. Comparative experiment 4: Investigation of catalytic system mixture and tertiary amine catalyst

[0317] In this comparative experiment, the effects of the catalyst system mixture and tertiary amine catalysts on the thermal conductivity of the material were investigated.

[0318] Experimental methods:

[0319] The thermal conductivity of the materials prepared in the above Examples 1-4 and Comparative Examples 7-8 was tested.

[0320] Result analysis:

[0321] Table 7. Thermal conductivity results of the embodiments and comparative examples

[0322]

[0323] From the above results, it can be seen that Examples 1-4 (using a complete catalyst system including organotin, organobismuth and perfluoroolefin) show lower thermal conductivity (0.0133 to 0.0138 W / m·K). This indicates that the complete combination of catalysts can effectively control the reaction rate, thereby forming a small and uniform bubble structure, which can effectively reduce heat conduction because smaller bubbles provide more thermal resistance and reduce the flow of heat.

[0324] Comparative Example 7 (lacking organotin and organobismuth) has a higher thermal conductivity (0.0190 W / m·K). The lack of these components results in a slower reaction rate and excessive or uneven bubble growth, which reduces thermal resistance and increases the thermal conductivity of the material.

[0325] The thermal conductivity of Comparative Example 8 (lacking perfluoroolefin) and Comparative Example 9 (lacking TOYOCAT-SX60 tertiary amine catalyst) is also relatively high (0.0173 and 0.0176 w / m·k). Perfluoroolefin and tertiary amine catalysts promote faster reaction speeds and help form smaller and more uniform bubbles, thereby improving the thermal insulation properties of the material. It should be noted that the role of catalysts in the preparation of polyurethane rigid foam is mainly to regulate the reaction speed and balance, which directly affects the generation of bubbles (that is, the cells of the foam). Catalysts enable chemical reactions to reach equilibrium faster, helping to form smaller and more evenly distributed bubbles:

[0326] Small bubbles can increase the total area of ​​the material's internal interface, thereby increasing thermal resistance during heat transfer. A more uniform distribution of bubbles can ensure structural consistency throughout the material, which is critical for reducing thermal conductivity.

[0327] The fast reaction can limit the growth of bubbles and prevent the formation of large bubbles. Large bubbles create larger cavities in the material, causing heat energy to transfer more easily through the material.

[0328] Based on the above analysis, experimental data show that a complete and efficient catalytic system can significantly improve the thermal insulation performance of polyurethane rigid foam. By controlling the dynamic balance of the reaction and accelerating the speed of the chemical reaction, it helps to form a small and uniform bubble structure, thereby optimizing its thermal conductivity. This illustrates the importance of accurately controlling the catalyst ratio and type in the rigid foam preparation process.

[0329] 5. Comparative experiment 5: Investigating the impact of different altitudes on materials

[0330] In this comparative experiment, polyurethane rigid foam materials were prepared at different altitudes in order to investigate the effects of altitude, atmospheric pressure and other parameters on the properties of the materials.

[0331] Experimental methods:

[0332] The thermal conductivity of the material prepared in the above Example 5 was tested.

[0333] Result analysis:

[0334] Table 8. Thermal conductivity results of the embodiments and comparative examples at different altitudes and atmospheric pressures

[0335]

[0336] (1) Based on the results in the above table (the unit of thermal conductivity in the table is w / m·k) and Figure 3 It can be seen that in Example 5, the polyurethane rigid foam materials prepared at four altitudes have a slightly increased thermal conductivity from 0.0133 to 0.0140 w / m·k as the altitude increases. The mean value of the thermal conductivity is 0.0137, and the difference between the data can be seen through the standard deviation, which is 0.000269. This shows that at higher altitudes (lower atmospheric pressure), the expansion of the bubbles is more significant, resulting in larger bubbles and weakened continuity of the foam structure, which leads to increased heat transfer efficiency.

[0337] (2) In Comparative Example 10, the formula of Example 5 was adopted, but the second low-boiling point foaming agent was removed. The thermal conductivity of the polyurethane rigid foam materials prepared at four altitudes ranged from 0.0152 to a maximum of 0.0192. The thermal conductivity obtained at an altitude of 2320 meters differed by 0.004 from that obtained at an altitude of 23 meters. The highest altitude was 1.263 times that of the lowest altitude. The average value was 0.0173 and the standard deviation was 0.001477. Comparative Example 11 adopted the formula of Example 5, but no tertiary amine catalyst was added. The thermal conductivity of the polyurethane rigid foam materials prepared at four altitudes ranged from 0.0175 to a maximum of 0.0202. The thermal conductivity obtained at an altitude of 2320 meters differed by 0.0027 from that obtained at an altitude of 23 meters. The highest altitude was 1.154 times that of the lowest altitude. The average value was 0.0189 and the standard deviation was 0.001190.

[0338] (3) The thermal conductivity of Comparative Examples 10 and 11 is generally higher than that of Example 5, and increases more significantly with increasing altitude. This is related to the lack of key components (second low boiling point blowing agent or tertiary amine catalyst), which makes the foam structure more susceptible to impact at high altitudes.

[0339] The data of Comparative Example 10 (no second low boiling point blowing agent added) and Comparative Example 11 (no tertiary amine catalyst added) show that the absence of these ingredients significantly increases the thermal conductivity of the material at higher altitudes. This indicates that these ingredients play a key role in maintaining the stability of the foam structure and reducing the bubble size.

[0340] (4) From the perspective of standard deviation, the gaps between the four groups of data in Comparative Example 10 and the differences between the four groups of data in Comparative Example 11 are significantly different from the gaps between the four groups of data in Example 5. The standard deviation corresponding to Comparative Example 10 is 0.001477, which is 0.001208 more than that in Example 5 and is 5.491 times that in Example 5. The standard deviation corresponding to Comparative Example 11 is 0.001190, which is 0.000921 less than that in Example 5 and is 4.424 times that in Example 14.

[0341] In summary, the thermal conductivity of Example 5 varies little at different altitudes (standard deviation 0.000269), indicating that the preparation process and material properties are relatively stable. The standard deviations of Comparative Examples 10 and 11 are larger, indicating that their performance fluctuates greatly at different altitudes, which may be related to the instability of the bubble structure inside the material.

[0342] At different altitudes, changes in atmospheric pressure will directly affect the bubble formation and stability of polyurethane rigid foam:

[0343] It should be noted that in a low-pressure environment (high altitude), the difference between the air pressure inside the bubble and the external air pressure increases, making the bubble easier to expand, resulting in an increase in the bubble volume. The bubble wall may become thinner, reducing its insulation effect and causing an increase in thermal conductivity.

[0344] The second low-boiling point blowing agent and tertiary amine catalyst are crucial to the control of reaction rate and bubble generation. The lack of these components makes it more difficult to maintain small and uniform bubbles in the material under low-pressure environment, affecting the thermal conductivity of the material.

[0345] It can be seen that when preparing polyurethane rigid foam materials, as the altitude increases, the corresponding air pressure becomes lower, and the air pressure in the bubbles generated during the reaction is high, which will cause partial bubble breakage or the gas in the bubbles to be discharged, and the outside air will enter the material, resulting in an increase in the thermal conductivity of the polyurethane rigid foam material. When the second low-boiling point foaming agent and tertiary amine catalyst are added at the same time, the toughness and strength of the bubble wall can be significantly improved, which will greatly reduce the gas replacement. At the same time, the vapor pressure of the gas in the bubble is small, which can also reduce bubble breakage and gas replacement, thereby greatly reducing the influence of the atmospheric pressure corresponding to the altitude on the thermal conductivity of the polyurethane rigid foam material during the preparation process.

[0346] In conclusion, the above analysis shows that the increase in altitude has a significant impact on the thermal conductivity of polyurethane rigid foam materials, especially when key components such as the second lowest boiling point blowing agent and tertiary amine catalyst are missing. When designing and selecting materials and their formulations, the altitude and atmospheric pressure of the environment in which they are used need to be considered to ensure that the materials can maintain excellent performance under different conditions.

[0347] The above are preferred implementation modes and corresponding embodiments of the present invention. It should be pointed out that, for those skilled in the art, without departing from the creative concept of the present invention, several modifications and improvements may be made, including but not limited to the adjustment of proportions, processes, dosages and reaction vessels, which all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a polyurethane rigid foam material, characterized in that: include: Dehydration treatment of polyether substances; Respectively prepare a polyether substance, a catalyst system mixture, a first low-boiling point blowing agent, a second low-boiling point blowing agent, a tertiary amine catalyst, a quality assurance agent and polymeric MDI, and divide the first low-boiling point blowing agent into part A and part B, and divide the second low-boiling point blowing agent into part C and part D; The catalyst system mixture comprises: organic tin, organic bismuth and perfluoroolefin; The tertiary amine catalyst is TOYOCAT-SX60; the first low-boiling point blowing agent is selected from at least one of pentane, methyl formate, HFC-245fa, LBA, R600, R600a, R152a, R134a, R1234yf, opteon 1100 / 1150, HCFO-1224yd, HCFO-1234ze, HCFO-1243zf, HCFO-1233xf and trifluoropropylene; the second low-boiling point blowing agent includes neopentane, tetramethylsilane and hexafluoropropylene; A combined polyether mixture is prepared by using the dehydrated polyether substance, the catalyst system mixture, part A of the first low-boiling point foaming agent, part C of the second low-boiling point foaming agent, the tertiary amine catalyst and the quality assurance agent; A polymeric MDI mixture is prepared using the polymeric MDI, part B of the first low-boiling point foaming agent, and part D of the second low-boiling point foaming agent; The combined polyether mixture and the polymerized MDI mixture are mixed and reacted, and microwave heating treatment is performed during the reaction process to obtain the polyurethane rigid foam material; the microwave heating treatment time is: heating to 30 seconds to 200 seconds after the reaction starts; the microwave heating treatment frequency is: 1.5 GHz to 3.2 GHz; The preservatives include isotridecyl alcohol and cocamide; The dehydration treatment is performed by heating and vacuum drying; the vacuum degree of the dehydration treatment is 0.02 MPA~0.04 MPA; the standard of the dehydration treatment is: controlling the water content of the polyether substance to be no more than 0.

01.

2. The method for preparing a polyurethane rigid foam material according to claim 1, characterized in that: In the combined polyether mixture, the weight proportions of the various raw materials are respectively: Polyether substances after dehydration treatment are 74~95.5; Catalytic system mixture 1~2; The first low boiling point foaming agent has a portion A of 0 to 5; 1 to 15 of the C portion of the second low boiling point foaming agent; Tertiary amine catalyst 0.5~1; Preservative 2~3.

3. The method for preparing a polyurethane rigid foam material according to claim 1, characterized in that: In the polymeric MDI mixture, the weight portions of each raw material are respectively: Polymeric MDI 80~100; The first low boiling point foaming agent has a B portion of 0 to 5; The D portion of the second low boiling point foaming agent is 0-15.

4. The method for preparing a polyurethane rigid foam material according to claim 1, characterized in that: The total weight percentage of A, B, C and D is 15-20.

5. The method for preparing a polyurethane rigid foam material according to claim 1, characterized in that: In the mixing reaction of the combined polyether mixture and the polymeric MDI mixture, the weight ratio of the polymeric MDI mixture to the combined polyether mixture is 1.2:

1.

6. The method for preparing a polyurethane rigid foam material according to claim 1, characterized in that: The temperature of the dehydration treatment is 60°C to 80°C.

7. The method for preparing a polyurethane rigid foam material according to claim 1, characterized in that: The dehydration time of the dehydration treatment is 60 min to 90 min.

8. The method for preparing a polyurethane rigid foam material according to claim 1, characterized in that: The polyether substances include: OTDA polyether, polyester, sorbitol polyether, silicone oil and amine catalyst.

9. The method for preparing a polyurethane rigid foam material according to claim 1, characterized in that: The polyether material includes the following components in parts by weight: OTDA polyether 56~77.5; Polyester 10~20; Sorbitol polyether 10~20; Silicone oil 1.5~2; Amine catalyst 1~2.

10. The method for preparing a polyurethane rigid foam material according to claim 1, characterized in that: The catalyst system mixture includes the following components in parts by weight: Organic tin 5~40; Organic bismuth 5~40; Perfluoroolefins 20~90.

11. The method for preparing a polyurethane rigid foam material according to claim 1, characterized in that: The second low boiling point foaming agent includes the following components in parts by weight: Neopentane 5~20; Tetramethylsilane 5~50; Hexafluoropropylene 60~90.

12. The method for preparing a polyurethane rigid foam material according to claim 1, characterized in that: The preservative includes the following components in parts by weight: Isotridecyl alcohol 20~50; Cocoamide 50~80.

13. A polyurethane rigid foam material, characterized in that: The polyurethane rigid foam material is prepared by the preparation method of the polyurethane rigid foam material according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Polyurethane foam

    CN101065414A

  • Polyether polyol, hard polyurethane foam and their production methods

    CN101528810A